1986
DOI: 10.1073/pnas.83.9.2979
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of human factor VIII: molecular forms in commercial factor VIII concentrate, cryoprecipitate, and plasma.

Abstract: Human factor VIII has been isolated from a high purity factor VIII concentrate by immunoaffmity chromatography and HPLC on Mono Q gel. Two fractions of factor VIII were obtained with a specific activity of w7000 units/mg.The major fraction contained eight peptide chains of 200, 180, 160, 150, 135, 130, 115, and 105 kDa plus one doublet chain of 80 kDa. The minor fraction contained one peptide chain of 90 kDa plus the chain of 80 kDa. Both fractions were activated by thrombin to the same extent. Amino-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
92
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 28 publications
6
92
0
1
Order By: Relevance
“…The factor-VIII complexes from nonactivated commercial concentrates. identified by SDSIPAGE analysis, are identical to those described by Anderson et al [7], and Fay et al [lo]. The prominent forms of factor VllI present, consisted of a light chain of 78 -80 kDa complexed with a heavy chain of 11 5 -210 kDa.…”
Section: Discussionsupporting
confidence: 65%
“…The factor-VIII complexes from nonactivated commercial concentrates. identified by SDSIPAGE analysis, are identical to those described by Anderson et al [7], and Fay et al [lo]. The prominent forms of factor VllI present, consisted of a light chain of 78 -80 kDa complexed with a heavy chain of 11 5 -210 kDa.…”
Section: Discussionsupporting
confidence: 65%
“…More or less proteolytically degraded forms of factor VIII have been found as active molecules in factor VIII material purified from therapeutic factor VIII concentrates (Andersson et al, 1986). The different forms of factor VIII, having molecular masses between 170-280kDa were shown to consist of one heavy chain, between 90-200 kDa, in combination with one 80-kDa light chain.…”
mentioning
confidence: 99%
“…Human factor VIII is synthesized as a single-chain molecule of approximately 300kDa and consists of the structural domains Al-A2-B-A3-CI-C2 Wood et al, 1984;Vehar et al, 1984;Toole et al, 1984). In newly drawn plasma prepared in the presence of protease inhibitors, factor VIII appears as a complex of two polypeptide chains of 200 and 80 kDa (Andersson et al, 1986). It has since been found that processing of the precursor product into these two polypeptide chains takes place in the Golgi apparatus (Kaufman et al, 1988).…”
mentioning
confidence: 99%
“…The B region, delimited by the amino acid residues 740 and 1648, is proteolyzed at different cleavage sites to generate active FVIII heterodimers of molecular mass ranging over 210000-80000 Da (including the total B domain) to 90000-80000 Da (without the B domain). Andersson et al [3] have shown that these different complexes have the same specific activity, suggesting that the B region is dispensable for FVIII procoagulant activity [4]. Nevertheless, the more efficient secretion observed for the different B-domain-deleted recombinant FVIII compared to the corresponding complete protein, suggests that this B region may be essential to regulate the FVIII biosynthesis [S].…”
mentioning
confidence: 99%